2013
DOI: 10.1002/ajh.23391
|View full text |Cite
|
Sign up to set email alerts
|

The combination of rituximab, bendamustine, and cytarabine for heavily pretreated relapsed/refractory cytogenetically high‐risk patients with chronic lymphocytic leukemia

Abstract: Treatment of patients with B-cell chronic lymphocytic leukemia (CLL) relapsed/refractory (R/R) to conventional treatments is particularly challenging. The combination of bendamustine and cytarabine has demonstrated distinct and synergistic mechanisms of action in preclinical studies on cell lines and primary tumor cells of several B-cell lymphomas, including 17p deleted or TP53 mutated CLL. The efficacy of rituximab (375 mg/m 2 , Day 1), plus bendamustine (70 mg/m 2 , days 1-2), and cytarabine (800 mg/m 2 , Da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 34 publications
(56 reference statements)
2
13
0
2
Order By: Relevance
“…The same benefit, on the contrary, has not been observed in the subset of del(17p) patients, were no CRs were registered and the response rate was only 25%. A recent study [18], reported an ORR of 78% for relapsed/refractory CLL patients with del(17p) treated with the combination of rituximab, bendamustine, and cytarabine, suggesting that the addition of cytarabine may overcome the resistance in this particular subset of patients, as also indicated by preclinical data [19].…”
Section: Discussionmentioning
confidence: 91%
“…The same benefit, on the contrary, has not been observed in the subset of del(17p) patients, were no CRs were registered and the response rate was only 25%. A recent study [18], reported an ORR of 78% for relapsed/refractory CLL patients with del(17p) treated with the combination of rituximab, bendamustine, and cytarabine, suggesting that the addition of cytarabine may overcome the resistance in this particular subset of patients, as also indicated by preclinical data [19].…”
Section: Discussionmentioning
confidence: 91%
“…от начала терапии ибрутинибом. Такие результаты можно объяснить коротким сроком на-блюдения [18] за этой когортой больных, поскольку известно, что del(17p) все же сохраняет неблагопри-ятное влияние на показатели выживаемости при терапии ибрутинибом. Так, согласно объединенному анализу результатов 3 исследований (PCYC-1102-1103, RESONATE, RESONATE-17), включавшему 243 пациента с del(17p), при медиане времени наблюдения 28 мес.…”
Section: Discussionunclassified
“…Одним из перспективных направлений в этой области является ингибитор тирозинкиназы Брутона -ибрутиниб, который показал свою эффек-тивность в терапии рецидивов ХЛЛ [16][17][18].…”
Section: Introductionunclassified
“…[6] The treatment for relapsed CLL is less standardized; repeated therapy with FCR or the use of BR is commonly employed in the relapse setting. [10,11] In the phase II trial of FCR in patients with relapsed CLL the ORR was 74%, with 30% CR. [9] The estimated median OS was 47 months and median PFS was 21 months.…”
Section: Expert Commentarymentioning
confidence: 99%